Avaliação postural e do sistema estomatognático em crianças e adolescentes - Motta, Lara Jansiski (2008)
The objective of this work was to investigate the relationship between craniocervical posture and bruxism, temporomandibular dysfunction (TMD) and mouth-breathing in different occlusal classes in children and adolescents. A cross-section, observational study was carried out, with 454 subjects. The posture analysis was carried out using photogrammetry and the software Alcimagem®. The diagnostic of bruxism was realized in accordance with the criteria of the American Academy of Sleep Medicine; the presence and severity of the TMD, was obtained using the Helkimo questionnaire; For the evaluation of respiration, the mirror clouding and filling the mouth with water tests were used and intrabuccal clinical exam for the classification of occlusal Angle. The data submitted to statistical analysis, using the program SPSS 12.0. The mean cervical angle of patients with bruxism (98.99°) was greater compared with those without bruxism (89.58°). The highest average cervical angulation was observed in the group with moderate TDM (97.59), followed by a mild degree (96.32º), and the lowest average (93.01º) in the patients with a severe degree. In relation to occlusal class, higher values for this angulation were observed in class II (96.77º± 8.79), compared with class I (90.64º±8.80) and class III (94.67º± 10.70). A larger cervical angle was observed for oral breathing group (96.59º) than for nasal breathing (86.60º). The differences were statistically significant. It was concluded that the children with bruxism in this study presented a greater alteration in head posture, compared with those without bruxism; there is a correlation between TMD, cervical posture and occlusion; in mouth breathing subjects, forward inclination of the head is predominant.